A guide to SQL - Pratt, Philip J.; Last, Mary Z. (Cengage Learning, 2015)
A GUIDE TO SQL, Ninth Edition, provides an effective introduction to SQL programming using straightforward instruction, extensive hands-on exercises, and a strong foundation in real-world business applications. The Ninth Edition builds on the longstanding success of this proven text by presenting basic SQL commands in the context of a running case, in which a business uses SQL to manage orders, items, customers, and sales reps. The authors emphasize that fundamental principles and practices apply regardless of the database environment chosen, and they include examples from the latest versions of Oracle® and Microsoft® Access®, and SQL Server throughout the text